PENGARUH TERAPI MINUM AIR PUTIH TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS DI WILAYAH KERJA PUSKESMAS TIGOBALEH BUKITTINGGI TAHUN 2023 - Aulia Putri; Cici Fazira; Anggraini, Dian (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2024)
Diabetes mellitus is a metabolic disorder disease characterized by an increase in blood sugar due to a deficiency of the hormone insulin and a decrease in the hormone insulin in the body which is predicted to continue to increase every year. One of the non-pharmacological techniques in controlling blood sugar levels is drinking water therapy. Study aims to determine the effect of drinking water therapy on reducing blood sugar levels in patients with diabetes mellitus. This quasy experiment is use non-equivalent control group design approach. The population is all people with diabetes mellitus. The sampling technique used purposive sampling of 30 people. Analysis included univariate analysis and bivariate analysis using the t-independent test. The results showed that the mean pre and post test blood sugar levels in the experimental group were 208 mg/dl and 188.40 mg/dl and the mean pre and post test blood sugar levels in the control group were 208.27 mg/dl and 204.40 mg/dl. There was a difference in the decrease in blood sugar levels between the control group and the experimental group with an average difference of 15.733 mg/dl and a p value = 0.000, the decrease in blood sugar levels was greater in the experimental group. The conclusions of this research are Drinking water therapy has a significant effect on reducing blood sugar levels in people with diabetes mellitus. Suggestions of this research are Study suggestion is ydrotherapy can be used as an intervention for hyperglycemia management and information in providing complementary therapy independently